The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5751/ace-01924-160212
|View full text |Cite
|
Sign up to set email alerts
|

Secretive marsh bird habitat associations in the Mississippi Flyway: a meta-analysis

Abstract: Secretive marsh birds, including rails and bitterns, have experienced widespread population declines due to the loss of wetland habitat on which they depend. Because of their cryptic behavior, secretive marsh birds are challenging to study and information on their habitat requirements is limited, especially across the full annual cycle. Quantifying habitat associations throughout the annual cycle and at broad geographic scales can advance a more comprehensive approach for secretive marsh bird conservation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…American bittern site colonization had a negative relationship with percent open water and no relationship with cover‐to‐water ratio, suggesting wetlands dominated by emergent vegetation may be preferable to American bittern. Other studies have reported negative relationships of marsh birds to open water areas, including sora during autumn migration in Missouri (Fournier et al 2018), and multiple species during the breeding season in the Prairie Pothole region (Malone et al 2021). Nevertheless, other research in the northern portion of the mid‐continent region shows inconsistent associations of SMBs to open water during the breeding season (Malone et al 2021).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…American bittern site colonization had a negative relationship with percent open water and no relationship with cover‐to‐water ratio, suggesting wetlands dominated by emergent vegetation may be preferable to American bittern. Other studies have reported negative relationships of marsh birds to open water areas, including sora during autumn migration in Missouri (Fournier et al 2018), and multiple species during the breeding season in the Prairie Pothole region (Malone et al 2021). Nevertheless, other research in the northern portion of the mid‐continent region shows inconsistent associations of SMBs to open water during the breeding season (Malone et al 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have reported negative relationships of marsh birds to open water areas, including sora during autumn migration in Missouri (Fournier et al 2018), and multiple species during the breeding season in the Prairie Pothole region (Malone et al 2021). Nevertheless, other research in the northern portion of the mid‐continent region shows inconsistent associations of SMBs to open water during the breeding season (Malone et al 2021).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations